Prosopography in historical research. Jorge Roa Martínez. Boyacá, 1891 – Pereira, 1966 - Tarazona, Álvaro Acevedo (Universidad Pedagógica y Tecnológica de Colombia, 2013)
The aim of this research article is to explore prosopography, considered from past times to be an autonomous discipline, and incorporated into contemporary historiographical  work for the study of the life trajectories of a given subject and of the social collective he/she belongs to. The analysis and systematization of indings of this research examine the life of a personality in the frame of what has been called intellectual history, as a history of culture, in the context of discussions on a historiographic topic that is more current every day.